Clinical characteristics and outcomes of intraocular lens dislocation: an eight-year retrospective study - Su Xu; Jingzhi Shao; Yuhang Zhang; Wei Si; Yi Mao; Shanshan Du; Fengyan Zhang (PLoS ONE, 2025)
Objective To investigate the clinical characteristics, risk factors, and short-term visual outcomes following surgical management of intraocular lens (IOL) dislocation, aiming to inform risk stratification and individualized treatment strategies. Methods A retrospective analysis was conducted on 155 patients (166 eyes) diagnosed with IOL dislocation between 2016 and 2024. Data collected included demographic information, ocular and systemic risk factors, surgical interventions, uncorrected distance visual acuity (UDVA) before and after surgery, and postoperative complications. Comparative analyses were performed to assess the short-term efficacy and safety of different surgical approaches. Results The mean patient age was 55 years, with 86.75% presenting unilateral dislocation. Predominant risk factors identified were high myopia (38.55%) and prior vitrectomy (17.47%). A total of 89.16% of IOL dislocations were classified as late-onset. Of the 154 eyes that underwent surgical intervention, both IOL repositioning and exchange procedures resulted in significant improvements in UDVA (P < 0.05). Postoperative transient intraocular pressure elevations were observed without significant differences between surgical methods, resolving within three days in all cases. Conclusion High myopia and prior vitrectomy are significant risk factors for IOL dislocation. Surgical correction, whether through repositioning or exchange, is effective and safe, leading to substantial visual acuity improvements. Proactive identification and management of high-risk individuals are crucial for preventing IOL dislocation and optimizing patient outcomes.